Structure theorems for families of idempotents - Kruhlyak, S. A.; Samoilenko, Yu. S. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
For *-algebras generated by idempotents and orthoprojectors, we study the complexity of the problem of description of *-representations to within unitary equivalence. In particular, we prove that the *-algebra generated by two orthogonal idempotents is *-wild as well as the *-algebra generated by three orthoprojectors, two of which are orthogonal.